A Feasibility Study of Off-the-Shelf Scalloped Stent-Grafts in Acute Type B Aortic Dissection. (December 2017) - van der Weijde, Emma; Bakker, Olaf J.; Kamman, Arnoud V.; van Herwaarden, Joost A.; Trimarchi, Santi; Vos, Jan Albert; Heijmen, Robin H.
Purpose: To evaluate the applicability of an off-the-shelf scalloped stent-graft to preserve left subclavian artery (LSA) flow in thoracic endovascular aortic repair (TEVAR) for acute type B aortic dissection.Methods: The computed tomography angiograms (CTA) of 70 consecutive patients (median age 64 years; 44 men) with acute Stanford type B aortic dissection were retrospectively analyzed to identify patients in whom a short proximal landing zone (<15 mm from the retrogradely dissected wall layers) would require LSA overstenting during TEVAR. A scalloped stent-graft was deemed possible in those patients with the intimal entry tear located at least 20 mm distant from the LSA ostium.Results: The LSA needed to be covered in 56 (80%) patients. Of these, an off-the-shelf scalloped stent-graft would have been applicable in 23 (41%) patients. In the latter group, the median aortic diameter was 31 mm (range 26–37), the median length of the LSA ostium was 13 mm (range 10–20), and the median width of the LSA ostium was 15 mm (range 11–24). Three differently sized off-the-shelf stent-grafts with the largest scallop possible could have adequately treated 20 (36%) of the 56 patients in the acute phase.Conclusion: In this single-center imaging-based study, involvement of the LSA in the setting of acute type B aortic dissection was seen in 80% of patients treated with TEVAR. Three off-the-shelf stent-grafts would suffice to treat one-third of these acute type B aortic dissections and may offer a relatively simple solution to preserve LSA flow, thereby lowering the risk of malperfusion of the (posterior) cerebrum, spinal cord, and left arm in an urgent/emergent setting.